Co-design and learning around diversification for resilient agrifood systems in Kenya - Waswa, Boaz Shaban; Muriithi, Catherine; Nyokabi, Miriam; Kagete, Eliud; Micheni, Alfred N.; Ooro, Patrick (2023)
Co-design and bundling various approaches are critical for facilitating information exchange and learning that are essential for wider adoption of sustainable intensification and climate smart agriculture technologies and practices. This blog highlights how this is being done under Ukama Ustawi in Embu County, Kenya.